2008
DOI: 10.1111/j.1540-8159.2009.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation and 30‐Minute Heart Rate Variability in Refractory Angina Patients

Abstract: (PACE 2009; 32:37-42) spinal cord stimulation, heart rate variability, refractory angina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In patients with refractory angina, a similar decrease in sympathovagal balance was also reported with SCS, assessed by the same method of spectral analysis of the heart rate variability. 35 The effects of SCS on sympathetic activity have also been reported in a number of other studies using different assessment methods: (i) in a rat model of mononeuropathy, SCS was reported to suppress pathological hyperexcitability of a wide dynamic of range spinal neurons after peripheral nerve lesions 36 ; (ii) in a number of animal studies led by Linderoth, the peripheral vasodilatory effects of SCS were linked to the inhibition of efferent sympathetic activity as noted in the current. [37][38][39][40] Improvement of GI motility resulting from the inhibition of the sympathetic activity has been reported in numerous previous studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In patients with refractory angina, a similar decrease in sympathovagal balance was also reported with SCS, assessed by the same method of spectral analysis of the heart rate variability. 35 The effects of SCS on sympathetic activity have also been reported in a number of other studies using different assessment methods: (i) in a rat model of mononeuropathy, SCS was reported to suppress pathological hyperexcitability of a wide dynamic of range spinal neurons after peripheral nerve lesions 36 ; (ii) in a number of animal studies led by Linderoth, the peripheral vasodilatory effects of SCS were linked to the inhibition of efferent sympathetic activity as noted in the current. [37][38][39][40] Improvement of GI motility resulting from the inhibition of the sympathetic activity has been reported in numerous previous studies.…”
Section: Discussionsupporting
confidence: 65%
“…The decrease in sympathetic activity and sympathovagal balance with SCS observed in this study suggests the involvement of the extrinsic autonomic pathway as we initially hypothesized. In patients with refractory angina, a similar decrease in sympathovagal balance was also reported with SCS, assessed by the same method of spectral analysis of the heart rate variability . The effects of SCS on sympathetic activity have also been reported in a number of other studies using different assessment methods: (i) in a rat model of mononeuropathy, SCS was reported to suppress pathological hyperexcitability of a wide dynamic of range spinal neurons after peripheral nerve lesions; (ii) in a number of animal studies led by Linderoth, the peripheral vasodilatory effects of SCS were linked to the inhibition of efferent sympathetic activity as noted in the current .…”
Section: Discussionmentioning
confidence: 59%
“…Similar autonomic mechanisms were also reported in previous studies in different clinical settings. Assessed by the same method of spectral analysis of HRV, SCS was found to decrease the sympathovagal ratio in patients with refractory angina and in diabetic rats . Assessed by total body norepinephrine, SCS was also noted to decrease overall sympathetic activity in patients with anginal pectoris .…”
Section: Discussionmentioning
confidence: 86%
“…In all 3 patients, there was an observation of significant reduction of TWA magnitude associated with SCS therapy 15 . Similarly, improvements in heart rate variability (HRV) have been associated with SCS angina therapy, particularly in reducing HRV measures of sympathetic activity (low/high frequency ratio) 16 . Another study, using a porcine animal model of ischemia and reperfusion, showed that SCS favorably impacts myocardial ischemic burden, infarct size, and arrhythmia risk 17 …”
Section: Editorial Commentmentioning
confidence: 94%
“…15 Similarly, improvements in heart rate variability (HRV) have been associated with SCS angina therapy, particularly in reducing HRV measures of sympathetic activity (low/high frequency ratio). 16 Another study, using a porcine animal model of ischemia and reperfusion, showed that SCS favorably impacts myocardial ischemic burden, infarct size, and arrhythmia risk. 17 Liu et al add several novel observations to those previously reported.…”
Section: Editorial Commentmentioning
confidence: 99%